Social Loafing on Empoyees: The Influences of Individual Level and Group Level Factors - Sri Wahyuni; Triani Arfah; Andi Tenri Pada Rustham; Patricia Cecilia Soharto (Pusat Penerbitan dan Publikasi Ilmiah, Fakultas Ekonomi dan Bisnis, Universitas Muslim Indonesia, 2022)
The success of group is determined by the completion of the tasks assigned to each member. However, not all group members can contribute as they should. Passive and less motivated individuals in completing group tasks refer to social loafing. This study aims to determine influence of individual and group factors on employees’ social loafing. This study conducted a quantitative approach with analyzing data from 30 employees. Our findings show that individual factors (task interdependence, task visibility, distributive justice, and procedural fairness) and group factors (group cohesiveness and perceived coworkers social loafing) do not influence social loafing behavior.